2018
DOI: 10.1136/bcr-2017-221801
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune haemolytic anaemia in a patient with advanced lung adenocarcinoma and chronic lymphocytic leukaemia receiving nivolumab and intravenous immunoglobulin

Abstract: We describe a rare case of severe autoimmune haemolytic anaemia (AIHA) in the setting of underlying chronic lymphocytic leukaemia receiving intravenous immunoglobulin, history of warm IgG autoantibody and treatment with nivolumab for advanced non-small cell lung cancer. In this report, we describe AIHA as a potential serious immune-related adverse event from immune checkpoint inhibitors, discuss other potential contributing factors and review previously described cases of AIHA in patients receiving programmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We identified 17 published cases of ICPi‐AIHA . The clinical and laboratory features of ICPi‐AIHA in these 17 cases are summarized in Supporting Information Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 published cases of ICPi‐AIHA . The clinical and laboratory features of ICPi‐AIHA in these 17 cases are summarized in Supporting Information Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Autoimmune hemolytic anemia (AIHA) occurs at a variable frequency, and it seems to be slightly more common with PD-1/PD-L1 inhibitors [ 62 ] The median time to onset is about 50 days, and mortality is nearly 15%. Some reports point to an association between ICI-induced AHAI and chronic lymphocytic leukemia, sugges-ting a potential increased risk of hematological immune toxicity in these patients [ 64 ]. Delanoy et al published a cohort of 35 cases (3 with chronic lymphocytic leukemia) and suggested to rule out the presence of an underlying chronic lymphocytic leukemia in any patient with a suspected immune-related hematological toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Besides durable and impressive clinical effects, ICIs could also induce multiple severe or even fatal organ system toxicities, including those of the hematological system. Frequently reported clinical hematological complications include neutropenia, 8 immune thrombocytopenia, 9 autoimmune hemolytic anemia, 10 and immune thrombocytopenic purpura 11,12 . ICI‐induced hematological AEs are rare but potentially life‐threatening events 10‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Frequently reported clinical hematological complications include neutropenia, 8 immune thrombocytopenia, 9 autoimmune hemolytic anemia, 10 and immune thrombocytopenic purpura 11,12 . ICI‐induced hematological AEs are rare but potentially life‐threatening events 10‐12 . However, these toxicities are sparsely reported in the related literature and their frequency, spectrum, and outcomes are still unclear.…”
Section: Introductionmentioning
confidence: 99%